2010
DOI: 10.2353/ajpath.2010.090872
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin (mTOR) Regulates Cellular Proliferation and Tumor Growth in Urothelial Carcinoma

Abstract: Mammalian target of rapamycin (mTOR) signaling has been associated with aggressive tumor growth in many cancer models, although its role in urothelial carcinoma (UCC) has not been extensively explored. Expression of phosphorylated mTOR (P-mTOR) and a downstream target, ribosomal S6 protein (P-S6), was identified in 74% (90/121) and 55% (66/121) of muscle-invasive UCCs, respectively. P-mTOR intensity and %positive cells were associated with reduced diseasespecific survival (P ‫؍‬ 0.04, P ‫؍‬ 0.08, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 36 publications
5
68
0
2
Order By: Relevance
“…Inhibition of mTOR signaling with rapamycin reduced cell proliferation and migration in vitro and reduced tumor volume in a T24-xenograft model by 55%. 71 These results were supported by a second study that showed mTOR activation in muscle-invasive UCC, 1,72 with mTOR inhibition preventing the progression of CIS to invasive bladder cancer. 72 Another important role of mTOR in tumor biology is the induction of angiogenesis.…”
Section: Role Of Mtor In Bladder Cancersupporting
confidence: 76%
See 1 more Smart Citation
“…Inhibition of mTOR signaling with rapamycin reduced cell proliferation and migration in vitro and reduced tumor volume in a T24-xenograft model by 55%. 71 These results were supported by a second study that showed mTOR activation in muscle-invasive UCC, 1,72 with mTOR inhibition preventing the progression of CIS to invasive bladder cancer. 72 Another important role of mTOR in tumor biology is the induction of angiogenesis.…”
Section: Role Of Mtor In Bladder Cancersupporting
confidence: 76%
“…71 One recent study has identified phospho-S6-a marker of mTOR activity-expression in 55% of muscle-invasive UCCs, with increased expression evident in paired lymph node metastases. The mTOR pathway activity was associated with reduced patient survival and increased pathological stage.…”
Section: Role Of Mtor In Bladder Cancermentioning
confidence: 99%
“…It is likely that other canonical and noncanonical signaling effects of TGF-b can occur in bladder cancer cells, especially given that SMAD2 can influence baseline mTORC2 activity and may affect the activity of mTORC1. Prior studies by our laboratory have shown a critical role for mTORC1 activity in bladder cancer cell proliferation and survival, rather than invasion, 36 although the role of TGF-b in this context is not known.…”
Section: Tgf-b/mtorc2 In Bladder Cancer Invasionmentioning
confidence: 95%
“…We have previously demonstrated that mTOR can influence bladder cancer cell migration and invasion, 7,36 primarily through effects on mTOR complex 2 (mTORC2) induction of RhoA activity. 7 Given the frequent alterations of TGF-b components in advanced bladder cancer and the ability of TGF-b to promote invasion in some cancer cell lines, we tested the ability of TGF-b to mediate motility effects in bladder cancer.…”
Section: Tgf-b Induces Mtorc2 Activity and Promotes Bladder Cancer Cementioning
confidence: 99%
“…Urothelial bladder carcinoma expresses mTOR signaling molecules, providing a rationale for clinical trials evaluating agents targeting this pathway (Tickoo et al, 2011). In fact, some studies using bladder cancer cell lines have demonstrated that sirolimus and related drugs inhibit the growth of cancer cells and decrease their viability (Fechner et al, 2009;Hansel et al, 2010;Pinto-Leite et al, 2009;Schedel et al, 2011). Similar results were obtained when treating bladder cancer animal models with sirolimus or everolimus (Chiong et al, 2011;Oliveira et al, 2011;Parada et al, 2011;Seager et al, 2009;Vasconcelos-Nóbrega et al, 2011).…”
Section: Preclinical Studiesmentioning
confidence: 99%